Attitudes and completion of advance care planning: Assessing the contribution of health beliefs about Alzheimer's disease among Israeli laypersons. Issue 6 (December 2019) - Werner, Perla; Schiffman, Ile Kermel
Abstract: Objectives: The purpose of this study was to assess laypersons' attitudes and completion of advance care planning (ACP) and to examine associations with sociodemographic characteristics and health beliefs on Alzheimer's disease. Methods: A cross-sectional telephone survey was conducted during April and May 2017, with a sample of 514 Israeli adults, aged 18 years and above. A structured, pretested questionnaire assessing participants' awareness, attitudes, and completion of ACP, as well as health beliefs on Alzheimer's disease (subjective knowledge, susceptibility, and worry), and sociodemographic factors, was used. Results: Two-fifths of the participants had heard of at least one of the terms: advance directives or durable power of attorney. Overall, participants expressed positive attitudes toward ACP. Results of regression models showed that gender, religiosity, and subjective knowledge of Alzheimer's disease were statistically significant correlates of attitudes toward ACP. Adding health beliefs on Alzheimer's disease doubled the amount of the variance explained, from 3% to 6%. Significance of results: Our results support the use of cognitive models of health behavior by assessing intra-personal beliefs and knowledge to understand ACP attitudes and completion. Specifically, we demonstrated the importance of knowledge of Alzheimer's disease for ACP attitudes, suggesting the importance of including a module on the topic to ACP interventions.